Critical success factors for new horizons in the supply chain of 3-D printed products – A review. (2021) - Singh, Satbir; Agrawal, Vivek
Abstract: 3-D printing is an emerging disruptive technology to disrupt existing manufacturing systems. This technology has tremendous potential to improve the quality and complexity of engineering products and also to raise the standard of life. Many big corporations and agencies are working to leverage this disruptive technology. This technology has not become as popular as the internet of things, etc. 3-D printing can help in sustainable operations via cost optimization, lead time reduction, safety incorporation, and better functionalities in the final products. The supply chain management of 3-D printed products is a must on digital platforms for the effective delivery of products and services of this evolving technology. No concrete study could be found that linked the supply chain management with the critical success factors of the 3-D printing industry. Hence this study was undertaken to understand the technical, economic, and managerial aspects that are critical for smooth operations of supply chains of 3-D printed products. This study is based on the literature review that includes various relevant articles available in the public domain regarding the supply chain of 3-D printed goods, 3-D printing industry reports, and research papers on Additive Manufacturing technology. The study concluded with the critical success factors for a customer-oriented supply chain of 3-D printed parts. Further research through case studies is required to study the bottlenecks and potential of improvements in the AM industry in some developed countries where 3-D printing manufacturers are in good numbers.